Four Methods to Estimate Minimum Miscibility Pressure of CO2‐Oil Based on Machine Learning. Issue 12 (11th November 2019) - Li, Ding; Li, Xiangliang; Zhang, Yinghua; Sun, Lixin; Yuan, Shiling
Summary of main observation and conclusion: CO2 flooding accounts for a considerable proportion in gas flooding. Using CO2 as a gas displacement agent is benefit for enhanced oil recovery (EOR), and the alleviation of the greenhouse effect by the permanent storage of CO2 in the crust. Minimum miscibility pressure (MMP) of CO2 ‐oil is a key factor affecting EOR, which determines the yield and economic benefit of crude oil recovery. Therefore, it is of great importance to use fast, accurate and cheap prediction methods for MMP estimation. In the present study, to evaluate the reliability of four recently developed prediction models based on machine learning ( i.e ., neural network analysis (NNA), genetic function approximation (GFA), multiple linear regression (MLR), partial least squares (PLS)), 136 sets of data are selected for calculation via outlier analysis from 147 sets of data. Afterwards, we compared the four models with existing prediction models from the literature. The analysis of correlation coefficients and multiple error functions shows that the four models can solve the MMP prediction problem well, and the model using intelligent algorithm has a higher prediction accuracy than the simple linear model. Besides, intelligent methods based on similarity algorithm have little difference from each other. Finally, a sensitivity analysis was conducted. Abstract : Four models based on machine learning, namely neural network analysis (NNA), genetic function approximation (GAF), multiple linear regression (MLR), and partial least squares (PLS) are proposed for prediction of minimum miscibility pressure of CO2 ‐oil.